Ameliorant Application on Variation of Carbon Stock and Ash Content on Peatland South Kalimantan - Siti Nurzakiah; Fahmuddin Agus; Haris Syahbuddin (UNIVERSITY OF LAMPUNG, 2013)
Carbon stock on peatlands are large and will be easily emitted if the land is opened or drained, therefore the measurements of carbon stocks and ash content are important to know the amount of emissions and agricultural sustainability in peatlands. This study aimed to determine carbon stock and ash content on peatlands in the Indonesia Climate Change Trust Fund (ICCTF) located in South Kalimantan on the geographic position S. 03°25’52